The Prevalence and Trend of Metabolic Syndrome in Mediterranean Regions: A Comprehensive Review - Nessren Ahmad Alduboie et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Metabolic Syndrome (MetS) is a cluster of interconnected conditions that increase the risk of cardiovascular disease, type 2 diabetes mellitus, and other chronic illnesses. These conditions include central obesity, hypertension, dyslipidemia, and insulin resistance. Mediterranean regions exhibit unique dietary, genetic, and lifestyle patterns that influence the prevalence of MetS. This review examines recent studies assessing the prevalence, trends, and contributing factors of MetS in Mediterranean populations. Key findings highlight regional differences, impacts of dietary habits, and the importance of lifestyle interventions in managing MetS in these regions. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/285 https://doi.org/10.5281/zenodo.14510792